Peningkatan Keterampilan Remaja Karang Taruna Dalam Digital Personal Branding Melalui Pelatihan Videografi di Kelurahan Bendo Kota Blitar - Roziana Febrianita; Chrystia Aji Putra; Latif Ahmad Fauzan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Karang Taruna is one of the community organizations focused on social affairs in society. Bendo Village, Blitar City, is one of the areas with potential for developing young community potential. Bendo Village already has a youth community called Karang Taruna. However, Karang Taruna in Bendo Village faces challenges that can hinder its development. One such challenge is the lack of ability to conduct organizational marketing or Personal branding through social media. To address this, videography-based Personal branding training was conducted with the aim of providing new understanding and skills to Karang Taruna in Bendo Village. The implementation method in this community service consists of preparation, briefing, training implementation, and monitoring evaluation. The Personal branding training conducted received a positive response from Karang Taruna members. With this positive response, it is hoped that in future activities, Karang Taruna in Bendo Village can further develop and improve their ability to conduct videography-based Personal branding on social media.